Profil Motivasi Kerja Terhadap Pedagang Kaki Lima (UMKM) Di Kota Surakarta - Asifa Nuriah Marganingrum; Fitriyani Wahyu Fatmawati; Lawrence Zada’anis Devinta; Nova Putri Dewi; Ryan Rasyid Ranuwijaya (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Motivation is the drive in life to achieve one of the motivations in one's life, namely work motivation. This study aims to analyze how much motivation traders have and analyze the influence of motivation on the performance of several traders in Surakarta City. The data collection method used in this study was with field interviews sourced from 7 traders in Surakarta City as a sample. The results of respondents' research were defined based on gender, age, length of business, turnover per day and motivation in trading. There is a picture of the motivation of traders in the high category. Based on the results of interviews, it can be seen that the 7 speakers consisted of 4 men and 3 women. On average, 7 interviewees have been trading for more than a year. Some traders settle in place, some go around. Various work motivations include meeting daily food needs, family needs, the desire to succeed, personal goals that want to be implemented immediately. So with some of these motivations, traders are enthusiastic about working their days.